Pulmonary Stenosis: Diagnostic Imaging and Respiratory Care Perspectives - Alanzi, Reem Shelewh; Miad Azooz Musa Alsalhani; Wesam Fayez Hammad Alshammari; Amjad Sulaiman Saket Alshammary; Fatimah Younis Ali Almohammedsaleh; Shoroq Ameer Almohammed Saleh; Mahdi Ali Alhelal; Yasseen Jafar Alabdrabalnabi; Haider Mohammed Almatar; Ahmad Albaqshi (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Pulmonary stenosis (PS) is a common congenital heart defect, accounting for 7-12% of cases, characterized by obstruction of the right ventricular outflow tract. It can occur in isolation or as part of complex syndromes. The clinical spectrum ranges from asymptomatic cases to severe presentations with heart failure. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This article provides a comprehensive review of PS, encompassing its etiology, pathophysiology, diagnostic evaluation, and contemporary management strategies to guide clinical practice. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A detailed narrative review was conducted, synthesizing current medical literature on PS. It examines diagnostic modalities, including echocardiography (the cornerstone), cardiac MRI, and CT, and analyzes evidence-based treatment guidelines from major cardiology societies. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The severity of PS dictates management. Mild, asymptomatic cases often require only surveillance. For significant valvular PS, balloon pulmonary valvuloplasty is the preferred first-line intervention, yielding excellent outcomes, particularly for domed valves. Dysplastic valves or complex/subvalvular obstructions often necessitate surgical repair. Critical PS in neonates is a ductal-dependent emergency requiring prostaglandin therapy and urgent intervention. Long-term prognosis is generally favorable with appropriate treatment, though complications like arrhythmias, pulmonary regurgitation, and endocarditis can occur. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> PS management requires accurate anatomical and hemodynamic assessment. Treatment is highly effective, ranging from monitoring to catheter-based or surgical interventions. A multidisciplinary, patient-tailored approach ensures optimal outcomes across the lifespan.